A dramatic world pandemic: SDGs and emerging legal issues - Torres-Cazorla, María Isabel (Iberoamerican Journal of Development Studies, 2022)
In this article, it is provided a bird’s-eye view on the so-called «emerging legal issues» and their relationship with the Sustainable Development Goals (SDGs) in times of pandemic. Firstly, there is a description of the topics that must be considered as «emerging legal issues»: unregulated topics, or in other words, subjects where the international regulation is unclear (or insufficient); for instance, a) environment, climate change, and disasters; b) scientific research, law, and human rights; c) law and new technologies, and d) culture and education. This is the starting point, because these topics must be confronted with the SDGs, to study the challenges of the international community to make them a reality. The SDGs must be reinterpreted and adapted to the reality left by COVID-19, in a realistic way. International cooperation is needed more than ever.